2004
DOI: 10.1128/aem.70.12.7192-7199.2004
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of the Gene Clusters Encoding Botulinum Neurotoxin Type A Complexes in Clostridium botulinum Type A, Ab, and A(B) Strains

Abstract: We describe a strategy to identify the clusters of genes encoding components of the botulinum toxin type A (boNT/A) complexes in 57 strains of Clostridium botulinum types A, Ab, and A(B) isolated in Italy and in the United States from different sources. Specifically, we combined the results of PCR for detecting the ha33 and/or p47 genes with those of boNT/A PCR-restriction fragment length polymorphism analysis. Three different type A toxin gene clusters were revealed; type A1 was predominant among the strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
47
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 39 publications
7
47
0
1
Order By: Relevance
“…It is assumed that food contamination reflects the prevalence of C. botulinum types in the environment where the food is prepared (6). This is consistent with the fact that C. botulinum A2 is frequent in southern Italy (8) and that the contaminated food from Corsica, which is close to Italy, also contains a subtype A2 strain.…”
supporting
confidence: 76%
“…It is assumed that food contamination reflects the prevalence of C. botulinum types in the environment where the food is prepared (6). This is consistent with the fact that C. botulinum A2 is frequent in southern Italy (8) and that the contaminated food from Corsica, which is close to Italy, also contains a subtype A2 strain.…”
supporting
confidence: 76%
“…PFGE is the current gold standard method used to differentiate strains of bacterial pathogens of public health significance, to assess the epidemic spread of infectious diseases in hospitals (32,48), and to trace food-borne outbreaks (1, 8, 36). Although PFGE is reproducible and discriminatory, some strains of C. botulinum types A and E have not been typeable using PFGE (20)(21)(22) due to DNA degradation, despite the use of formaldehyde prior to DNA isolation. In this study, however, we have shown that the addition of 50 M thiourea to the running buffer overcomes the problems of DNA degradation, with all 21 type E isolates that were previously untypeable now producing high-quality fingerprints.…”
Section: Discussionmentioning
confidence: 99%
“…PFGE and RAPD typing have revealed extensive genetic biodiversity among type E isolates (22,29). PFGE has recently been applied for typing outbreak strains of C. botulinum group I (20), but its usefulness during a food-borne outbreak investigation remains unknown, in part because of the low incidence of botulism outbreaks yielding isolates from clinical, food, and environmental sources (33).…”
mentioning
confidence: 99%
“…Yra skiriami septyni skirtingi botulino neurotoksino tipai (A, B, C, D, E, F, G). Medicinoje dažniausiai yra naudojamas botulino neurotoksinas A [32].…”
Section: Botulino Neurotoksinasunclassified